PENGEMBANGAN INSTRUMEN FOUR TIER-TEST PADA KONSEP USAHA DAN ENERGI - Apolonia Masiona Boro; Indica Yona Okyranida; Irnin Agustina Dwi Astuti (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2020)
The feasibility of the four tier-test instrument can be seen through validation results by experts (appraisal). Through validation of experts by using questionnaires, data obtained. The data obtained in the form of qualitative data is then converted into quantitative data by summing the score, then converted into percentages.Based on the results of the first material expert validation test with a percentage of 78.75% and the second material expert with a presentation of 77.50%. So the average material validation is 78.75%. This indicates that the development of four tier test infrastructure is feasible to measure misconceptions that occur in business concepts and energy.  Based on the results of the analysis that has been done as shown the development of four tier-test instruments on business concept and energy has an average number of 3.9 in the first expert and 3.8 in the second expert. Whereas if the average obtained a value of 3.85 with a category of feasibility is very good.